Child, body and language: what/who speaks - Borges, Sonia (Clinical Styles. The Journal on the vicissitudes of childhood, 2004)
There can be a convergence of the somatic or organic studies and the psychoanalysis, once the first two describe the phenomena and the late gives the reason for its structure. However, in the case of the adoption of a position in which the psychic causality, the subject of the unconscious and the criteria of transference are not recognized, one can incur in reductionism.